Good economics for hard times: better answers to our biggest problems - Banerjee, Abhijit V; Duflo, Esther (London Allen Lane, 2019)
The book draws from recent developments in economics research to argue solutions to the issues facing modern economies and societies around the world, including slowing economic growth, immigration, income inequality, climate change, globalization and technological unemployment. The authors challenge common assumptions and offer evidence-based recommendations, emphasizing a more compassionate and data-driven approach to policy. They advocate for using randomized controlled trials and other research methods to inform policies and address issues like immigration, trade, and automation.
Includes bibliographical references, index
mnn 10/06/2025
Loans
Keywords: Economic History; Economic policy; Poverty - Economic aspects; Globalization - Economic aspects; Social problems - Economic aspects; Inequality - Economic aspects; Globalization